Analysis of The Implementation of Prima Service Management to Increase Interest in Hajj and Umrah Pilgrimages Follow Manasik at HMC Payakumbuh - Asni, Asni; February, Andis; Rofiqi, Moh Arfin (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
Providing knowledge of Manasik is the task of the government and travel agencies organizing the Hajj and Umrah. The objective of holding rituals is To practice independence, as well as so that the congregation can carry out worship according to the guidance of the Prophet. However, there are still many in the holy land of the congregation who only rely on a guide while on the ground because they do not understand and do not know corners of the city of Mecca because they only manasic 3-4 times. There needs to be excellent service to attract their interest following the manasic class. This research aims to know the excellent implementation management service in HMC (Hijrah Muslim Center) Payakumbuh. The method used in the study This is method descriptive- a qualitative. Results show Organizer rituals in institution rituals HMC The Great Wall Already apply good service by service standards and principles of excellent service. Marked by the satisfaction felt by the congregation undergoing manasik at HMC. In addition to manasik for free, HMC also provides services to the congregation in the form of facilitating the congregation to complete the administrative requirements in the form of passport administration, meningitis vaccination, photos, provision of small gifts, exchange Money real, and savings Hajj And Umrah.